2012
DOI: 10.1177/0363546512462810
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Medial Opening Wedge Proximal Tibial Osteotomy on Patellofemoral Contact

Abstract: When performing a medial opening wedge proximal tibial osteotomy, the surgeon should consider the negative effects of increased patellofemoral peak pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 32 publications
(64 reference statements)
2
58
0
Order By: Relevance
“…Clinical appearance at 6 years after surgery indicated she had excellent clinical results. At the last clinical examination, the right knee score was 85 points and the left one 91 points there was a significant increase in patellofemoral pressures after medial opening wedge osteotomy of only ten millimetres and a larger osteotomy resulted in a greater increase [15]. The preliminary results of this study have supported the authors' hypothesis that the results of osteotomy might not depend on the presence of lateral compartment involvement, the severe degrees of osteoarthritic change and associated angular deformities.…”
Section: Discussionsupporting
confidence: 69%
“…Clinical appearance at 6 years after surgery indicated she had excellent clinical results. At the last clinical examination, the right knee score was 85 points and the left one 91 points there was a significant increase in patellofemoral pressures after medial opening wedge osteotomy of only ten millimetres and a larger osteotomy resulted in a greater increase [15]. The preliminary results of this study have supported the authors' hypothesis that the results of osteotomy might not depend on the presence of lateral compartment involvement, the severe degrees of osteoarthritic change and associated angular deformities.…”
Section: Discussionsupporting
confidence: 69%
“…Hinterwimmer et al [26] specified these complaints in patients with mid to severe patellofemoral arthritis as pain behind the patella during activities or under clinical examination. Moreover, it was shown that there was a significant increase in patellofemoral pressures after medial opening wedge proximal tibial osteotomies of only 10 mm (larger osteotomies resulted in a greater increases) [31]. To avoid these postoperative drawbacks (patella infera, high patellofemoral pressures) in these cases (preoperative patellofemoral arthritis and pain, great correction angles ≥10°), the frontal plane osteotomy was aimed distally, leaving the tuberosity on the proximal fragment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented the effects of HTO on the biomechanics of the knee . Opening wedge HTO may lead to increased patellofemoral peak pressure .…”
mentioning
confidence: 99%
“…Previous studies have documented the effects of HTO on the biomechanics of the knee . Opening wedge HTO may lead to increased patellofemoral peak pressure . A moderate‐to‐large increase in the valgus alignment of the lower limb can result in decreased contact pressures in the medial compartment .…”
mentioning
confidence: 99%